Memupuk Harapan Pertanian Indonesia: Kontribusi Generasi Muda dalam Peningkatan Teknologi Demi Mewujudkan Pertanian Indonesia yang Berkelanjutan: Nurturing the Hope of Indonesian Agriculture: Young Generation's Contribution to Technology Improvement for Sustainable Indonesian Agriculture - Hidayatullah, Rahmat Syarif; Rozaki, Zuhud; Wulandari, Retno; Azzahra, Isni (Universitas Muhammadiyah Yogyakarta, 2024)
Qualified human resources who are committed to creating a quality agricultural sector are one of the success factors for sustainable agricultural development. However, the current condition of agriculture faces a serious problem, namely the number of young farmers has decreased. The role of farmers is very important to fulfill the food needs of a country. With the decreasing number of farmers today and the average farmer is old, it can threaten overall food security. Family as an internal factor plays an important role in the regeneration of farmers where they can directly interact at any time. The role of the government and the private sector in land conversion policies needs to pay attention to the impacts caused. . In the midst of globalization and the development of information technology, the strengthening of the three extension models has been challenged by the innovation of information production and distribution mechanisms to complement farmers' decision-making. Extension communication systems based on information technology or new media need to be an important concern, especially to stimulate the development of the interest of young farmers who are increasingly literate with the application of renewable technology.